Военная экспансия Российской империи и захват казахских земель в Северном Казахстане (1752-1755 гг.) - Кабульдинов, З.Е. (Культура народов Причерноморья, 2013)
В этой статье автор исследует процесс открытой аннексии Российской империей
казахских земель в Северном Казахстане применительно к середине 18 века. Исследователь на основе
архивных и письменных источников делает вывод о том, что в период заключительной стадии казахско-джунгарского противостояния царизм приступил к агрессивной политике отторжения земель своих
новых подданных. У цій статті автор досліджує процес відкритої анексії Російською імперією казахських
земель в Північному Казахстані стосовно середині 18 століття. Дослідник на основі архівних та
письмових джерел робить висновок про те, що в період заключної стадії казахсько-джунгарского
протистояння царизм приступив до агресивної політики відторгнення земель своїх нових підданих. In this article, the author explores the process of open annexation by the Russian Empire Kazakh
lands in northern Kazakhstan in relation to the mid-18th century. Researcher on the basis of archival and
written sources, concludes that during the final stage of the Kazakh – Zhungar confrontation tsarist government
began an aggressive policy of exclusion of lands of their new subjects. The process of Kazakh – Zhungar
confrontation in the early 50s of the XVIII century coincided with the activation of the tsarist military machine in
Northern Kazakhstan and South West Siberia. The Russian Empire, is about taking part Kazakhs Younger and
Middle zhuzes in their citizenship without waiting for the final strengthen their borders in the former Kazakh
encampments, embarked on the further continuation of large-scale land grabbing his new subjects.
As the written and archival sources, the issue of transferring staroishimskoy line deep into the Kazakh nomads
did not come at once and has a little history. Not yet had time to bring the tip of the Kazakhs of the Middle
Horde oath of allegiance to the Russian Empire, as the tsarist government immediately moved to the drafting on
the nomination of the boundary line deep into the northern Kazakh nomads. The essence of the plan Kutuzov was
that the new boundary line was to be near the "big road connecting Siberian jails". But the plan was eventually
rejected because they did not quite take into account the natural and geographical and military-political
characteristics of the region. Tsarist government, knowing aggravated relations and Bashkirs and Kazakhs are
able to extract some benefit for himself by opposing them to each other, taking advantage of the intensification of
conflict between them, especially after the events of 1755: this line as a border guard and began to serve a
significant the number of servicemen of the Bashkirs.
As a result of a "new line", the Russian frontier was pushed into the nomads of the Middle Horde to 200 – 250
miles. This, of course, could not break the existing system migrations, deprived generations of traditional
Kazakh pastures, now trapped inside the boundary lines. Kazakhs are forever lost their land, now suddenly
found themselves inside the boundary line.
Thus, in 1752 the tsarist government began a major seizure of Kazakh lands on the Siberian line is in the form of
"extension" of the original boundary lines. As a result of these actions, the Kazakhs have been moved for a new
feature, much to "deepen" in the traditional nomadic Middle Horde to 250 miles. Kazakhs again lost a
significant body of their ancestral land, is approximately 75,000 square kilometers. This fact should cause
indignation Kazakhs, later fell deeply in "unauthorized" transitions and attacks on this site boundary line.
However, they later turned into an ordinary horse stealing. These actions Kazakhs could not affect the formation
of the specific demographic situation in the border with the steppe domestic constituencies - Kurgan and Ishim.
Facts raids, "illegal" from a position of tsarist migrations Kazakhs to the "inner side" should not be seen as a
way to develop new land, and as an attempt to return to their native-tribal land alienated the tsarist government
in 1752 – 1755 as a result of its colonial expansion.